Electronic cigarettes as a smoking cessation aid for patients with cancer: beliefs and behaviours of clinicians in the UK. Issue 11 (19th November 2020) - Brett, Jo; Davies, Emma L; Matley, Fiona; Aveyard, Paul; Wells, Mary; Foxcroft, David; Nicholson, Brian; De Silva Minor, Shiroma; Sinclair, Lesley; Jakes, Sarah; Watson, Eila
Abstract : Objectives: To explore UK clinicians' beliefs and behaviours around recommending e-cigarettes as a smoking cessation aid for patients with cancer. Design: Cross-sectional online survey. Setting: England, Wales, Scotland and Northern Ireland. Participants: Clinicians involved in the care of patients with cancer. Primary and secondary outcomes: Behavioural Change Wheel capability, opportunity and motivation to perform a behaviour, knowledge, beliefs, current practice around e-cigarettes and other smoking cessation practices. Method: Clinicians (n=506) completed an online survey to assess beliefs and behaviours around e-cigarettes and other smoking cessation practices for patients with cancer. Behavioural factors associated with recommending e-cigarettes in practice were assessed. Results: 29% of clinicians would not recommend e-cigarettes to patients with cancer who continue to smoke. Factors associated with recommendation include smoking cessation knowledge (OR 1.56, 95% CI 1.01 to 2.44) and e-cigarette knowledge (OR 1.64, 95% CI 1.06 to 2.55), engagement with patients regarding smoking cessation (OR 2.12, 95% CI 1.12 to 4.03), belief in the effectiveness of e-cigarettes (OR 2.36 95% CI 1.61 to 3.47) and belief in sufficient evidence on e-cigarettes (OR 2.08 95% CI 1.10 to 4.00) and how comfortable they felt discussing e-cigarettes with patients (OR 1.57 95% CI 1.04 to 2.36). Conclusion: Many clinicians providing cancer care to patients who smoke do not recommend e-cigarettes as a smoking cessation aid and were unaware of national guidance supporting recommendation of e-cigarettes as a smoking cessation aid.